BIOMASSA DAN KARBON POHON DI ATAS PERMUKAAN TANAH DI TEPI JALAN TAMAN NASIONAL LORE LINDU (Studi Kasus Desa Sedoa Kecamatan Lore Utara Kabupat - Sedjarawan, Wahyu; Akhbar, Akhbar; Arianingsih, Ida (Universitas Tadulako, 2014)
The objectives of this study were to determine the biomass and tree carbon along side of Lore Lindu National Park. The research was conducted at Sedoa village, Lore Utara district, Poso Regency, Central Sulawesi from May to August 2013. Estimation of carbon stock was done by non-destructive method by using allometric formula.There were four observation plots, where each two plots were placed with distance 10 m and 100 m fromÂ the main road alongside Lore Lindu National Park. The results showed that the biomass total of the trees aboveground were 711.0 ton ha-1 and 256.0 ton ha-1in plots that placed with distance 10 m and 100 m from the main road along side Lore Lindu National Park, respectively. Hence, based on the biomass calculation, the total carbon of the tree aboveground wereÂ 355.6 ton ha-1 and 128.0 ton ha-1 in plots that placed with distance 10 m and 100 m from the main road along side Lore Lindu National Park, respectively. Keywords: Biomass, Tree Carbon, Lore Lindu National Park.